Analisis Strategi Pembelajaran Berbasis Masalah (SPBM) Terhadap Kesulitan Membaca Permulaan Pada Peserta Didik Kelas 2 MIS Kertajaya II Mangunjaya Pangandaran Jawa Barat - Dinatun Nasyhah; Robingun Suyud El Syam; Nur Farida (Journal of Student Research, 2024)
This study examines the types and factors of reading difficulties in children at MIS Kertajaya II Mangunjaya, as well as evaluating the application of Problem-Based Learning Strategies (SPBM) implemented by classroom teachers. This qualitative research used observation, interview and documentation methods to collect data. The results showed that 8 students experienced reading difficulties, with various types of difficulties such as difficulty seeing long distances, low memory, difficulty spelling and pronouncing letters, and lack of letter recognition. Teachers at MIS Kertajaya II Mangunjaya implemented SPBM with the method of showing animated videos, using everyday problems, letter card media, and remedial programs to overcome students' reading difficulties. SPBM proved effective with the support of adequate infrastructure, but was hampered by unconducive classroom conditions. This study also identified the types and factors of reading difficulties at MIS Kertajaya II Mangunjaya and evaluated the effectiveness of SPBM in overcoming them. The implementation of SPBM proved to be beneficial, but needs adjustments to maximize its effectiveness.